The Impact of Barns Microclimate Modification on the Beef Cattles Physiological Responses Raised in the Peatlands of Central Kalimantan - A. Yani; Adrial; R. Priyanto; Salundik; L. Abdullah; S. Prabowo (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2024)
This study aimed to evaluate the effect of cattle barns microclimate modification on the physiological response of beef cattles reared on peatland. This study used direct observation and experimental research methods. Microclimate modification is done by using asbestos material, gable roof type and roof height ≥3.5 meters, and vegetation arrangement. Data were collected through measurements of microclimatic parameters and physiological responses in the morning (06.30–07.30), at noon (11.30–12.30), and in the afternoon (16.30–17.30), with measurement intervals every month. The number of cattle barns observed was 46 units. The physiological parameter measurements involved 124 female beef cattle, consisting of 70 Bali and 54 crossbred cattle with physiological stages, gestating cows and lactation period. The results showed that modifying cattle barns and the surrounding environment can reduce the microclimate in the cattle barn as indicated by a decrease in THI from emergency to dangerous levels during the noondayand from dangerous to caution levels in the afternoon. The improvement in microclimate conditions was also followed by a decrease in the level of heat stress as indicated by a decrease in the physiological responses of cows.